1999
DOI: 10.1086/307548
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and Multiwavelength Variability of the Blazar 3C 279: Evidence for Thermal Emission

Abstract: The γ-ray blazar 3C 279 was monitored on a nearly daily basis with IUE, ROSAT and EGRET for three weeks between December 1992 and January 1993. During this period, the blazar was at a historical minimum at all wavelengths. Here we present the UV data obtained during the above multiwavelength campaign. A maximum UV variation of ∼50% is detected, while during the same period the X-ray flux varied by no more than 13%.At the lowest UV flux level the average spectrum in the 1230-2700Å interval is unusually flat for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 59 publications
11
109
0
1
Order By: Relevance
“…estimated in Celotti, Padovani, & Ghisellini (1997) from the observed emission lines (see also Francis et al 1991) as ergs s~1. This value corresponds to D30% L BLR \ 6 ] 1044 of the accretion disk luminosity estimated by Pian et al (1999) from the UV observations during the 1993 campaign. Applying the model to the 1993 state, the one with lowest emission, we found that the best reproduction was obtained for an energy density ergs cm~3 ; this correu BLR D 10~4 sponds to a BLR radius cm, consistent R BLR \ 4 ] 1018 with the value obtained from the relation found R BLR -L BLR by Kaspi et al (2000).…”
Section: Discussionmentioning
confidence: 73%
“…estimated in Celotti, Padovani, & Ghisellini (1997) from the observed emission lines (see also Francis et al 1991) as ergs s~1. This value corresponds to D30% L BLR \ 6 ] 1044 of the accretion disk luminosity estimated by Pian et al (1999) from the UV observations during the 1993 campaign. Applying the model to the 1993 state, the one with lowest emission, we found that the best reproduction was obtained for an energy density ergs cm~3 ; this correu BLR D 10~4 sponds to a BLR radius cm, consistent R BLR \ 4 ] 1018 with the value obtained from the relation found R BLR -L BLR by Kaspi et al (2000).…”
Section: Discussionmentioning
confidence: 73%
“…This lower limit to the temperature (and consequently to the luminosity) is constrained by the break of the SED in the optical-UV transition, but much hotter and hence more luminous discs are possible. For comparison, the thermal disc fitted by Pian et al (1999) to the UV data of 3C 279 has a temperature of 20 000 K and a luminosity of 2 × 10 45 erg s −1 .…”
Section: The Helical Jet Modelmentioning
confidence: 99%
“…The most extreme variability patterns include intraday variability with flux decays of P0.1 mag hr À1 ( Kartaltepe & Balonek 2007). Observations with the International Ultraviolet Explorer in the very low activity state of the source in 1992 DecemberY1993 January revealed the existence of a thermal emission component, possibly related to an accretion disk, with a luminosity of L UV $ 2 ; 10 46 erg s À1 if this component is assumed to be emitting isotropically (Pian et al 1999). Pian et al (1999) also identified an X-ray spectral variability trend in archival ROSAT data, indicating a lag of $2Y3 days of the soft X-ray spectral hardening behind a flux increase.…”
Section: Introductionmentioning
confidence: 99%